2013
DOI: 10.1038/labinvest.2013.40
|View full text |Cite
|
Sign up to set email alerts
|

ROS-mediated downregulation of MYPT1 in smooth muscle cells: a potential mechanism for the aberrant contractility in atherosclerosis

Abstract: Reactive oxygen species (ROS) mediates the aberrant contractility in hypertension. Abnormal contractility occurs in atherosclerotic vessels but changes in proteins that regulate contractility remain poorly understood. Myosin phosphatase (MP) activity, which regulates smooth muscle relaxation, is regulated by the phosphorylation of its regulatory subunit, MP targeting subunit 1 (MYPT1). In the present study, we examined the roles of ROS in MP subunit expression both in cultured human aortic smooth muscle cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Previous studies have indicated that NAD(P)H oxidases are major factors involved in the aberrant production of ROS in the vasculature (7,8). Cumulative evidence has demonstrated that ROS are essential in the pathogenesis of various types of cardiovascular disease, including stroke and atherosclerotic lesions (9). ROS-mediated oxidative modification of phospholipids can damage endothelial cells and induce the expression of adhesion molecules, which leads to attachment of monocytes, T lymphocytes and macrophages to the endothelial cells (10).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that NAD(P)H oxidases are major factors involved in the aberrant production of ROS in the vasculature (7,8). Cumulative evidence has demonstrated that ROS are essential in the pathogenesis of various types of cardiovascular disease, including stroke and atherosclerotic lesions (9). ROS-mediated oxidative modification of phospholipids can damage endothelial cells and induce the expression of adhesion molecules, which leads to attachment of monocytes, T lymphocytes and macrophages to the endothelial cells (10).…”
Section: Introductionmentioning
confidence: 99%
“…However, ROS overproduction can further promote the inflammatory process and injure neighboring host cells and tissues by lipoperoxidation, proteolysis or DNA degradation (Braga et al, 2012;Mata-Campuzano et al, 2012;Tsumbu et al, 2011). Growing evidence suggests that an abnormal ROS production attributed to an absent regulation of PMNs respiratory burst is involved in the pathogenesis of various inflammatory disorders such as rheumatoid arthritis (Mirshafiey & Mohsenzadegan, 2008;Shah et al, 2011), atherosclerosis (Cheng et al, 2013;Ding et al, 2013), reperfusion injury (Gutowski & Kowalczyk, 2013;Madamanchi & Runge, 2013), and even cancer (Li et al, 2012). Thus, it is interesting to find antioxidative substances with the ability to inhibit ROS production and/or directly scavenge ROS formed in the process of respiratory burst.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this, estradiol has also been shown to produce a 2-3-fold increase in aortic smooth PPP1R12A expression in a mice model of atherosclerosis[27]. Smoothelin-1 is also known to represses PPP1R12A expression, but pregnancy related changes on MYPT expression are similar in both wild type and smoothelin-deficient mice[21,28].…”
Section: Resultsmentioning
confidence: 99%